2001
DOI: 10.1161/hh1801.096263
|View full text |Cite
|
Sign up to set email alerts
|

Fc Receptor–Mediated Inhibitory Effect of Immunoglobulin Therapy on Autoimmune Giant Cell Myocarditis

Abstract: Abstract-In the present study, the mechanisms and importance of the Fc portion of immunoglobulin in experimental giant cell myocarditis were examined. Giant cell myocarditis was induced in rats by immunization of porcine cardiac myosin.were administered intraperitoneally daily on days 1 to 21. Intact immunoglobulin administration significantly ameliorated myocarditis, but F(abЈ) 2 fragments did not. The ribonuclease protection assay revealed that therapy with intact immunoglobulin, but not F(abЈ) 2 fragments, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 24 publications
(26 reference statements)
4
82
2
Order By: Relevance
“…shown in previous studies, immunoglobulin antigenecity between different species does not appear to be a problem, 10,11,13 and furthermore both agents have the same chemical structure as the Fab portion of immunoglobulin.…”
Section: Effects Of Late Administration Of Immunoglobulin On Experimesupporting
confidence: 51%
See 1 more Smart Citation
“…shown in previous studies, immunoglobulin antigenecity between different species does not appear to be a problem, 10,11,13 and furthermore both agents have the same chemical structure as the Fab portion of immunoglobulin.…”
Section: Effects Of Late Administration Of Immunoglobulin On Experimesupporting
confidence: 51%
“…The therapy was first demonstrated to be effective for an autoimmune disorder (idiopathic thrombocytopenic purpura) 8 and since then, it has been established as effective in the treatment of Guillain-Barré syndrome, chronic inflammatory demyelinating polyneuropathy, myasthenia gravis, dermatomyositis and Kawasaki's syndrome, and in the prevention of graft-vs-host disease in recipients of allogenic bone marrow transplants. [8][9][10][11][12][13][14][15][16][17] Benefits have been reported for many other autoimmune and systemic inflammatory conditions, but controlled trials are often lacking.…”
Section: Discussionmentioning
confidence: 99%
“…At first glance their results appear to be contradictory to previous reports by our own group [15,16] by Gill et al [70] In our study, not only FcγRIIB-mediated inhibitory effect on experimental autoimmune myocarditis in rats [15] but FcγRIIB-mediated antiatherosclerotic effect in apolipoprotein E-deficient mice [16] were demonstrated, using immunoglobulin preparations. Gill et al [70] demonstrated the targeting effect of immunoglobulin on adhesion molecules using ischemia reperfusion model in cats, suggesting the down regulation of adhesion molecules via Fc receptors.…”
Section: Fcγ Receptors and C-reactive Proteincontrasting
confidence: 99%
“…An in vitro study showed that intact immunoglobulin, but not F(ab') 2 Fragments, suppressed the lipopolysaccharide-induced interleukin-1β production associated with the down regulation of CD32 antigen (Fcγ receptor II) expression. Thus, intact immunoglobulin therapy markedly suppressed myocarditis as a result of Fc receptormediated anti-inflammatory action, and the suppression of the disease was associated with the suppression of DCs, ie, the suppression of the initial antigen-priming process in experimental giant cell myocarditis [15]. Altogether, FcγRIIB-mediated inhibitory action is highly involved [16].…”
Section: Theoretical Backgrounds Of Fcγr System In Myocardial Diseasesmentioning
confidence: 98%
“…14,15 Moreover, immunoglobulin therapy suppressed experimental giant cell myocarditis in rats associated with the suppression of the expression of dendritic cell via inhibitory Fc receptor. 16 Because the leukocyte count was immediately decreased by the treatment, anti-inflammatory effects of immunoglobulin were shown in this study and, moreover, it may be because of the immunomodulatory effects of immunoglobulin that the patient's condition rapidly recovered, as spontaneous recovery of cardiac functions is in general slow in patients with acute myocarditis. 1,17 Increasing evidence supports the role of local and systemic oxidative stresses in the development and severity of myocarditis and cardiomyopathy.…”
Section: Discussionmentioning
confidence: 53%